2012
DOI: 10.5861/ijrsp.2012.157
|View full text |Cite
|
Sign up to set email alerts
|

Relations among children’s theory of mind, family factors, language development, and story comprehension in L1 and L2 preschoolers

Abstract: This study examined the relation of family factors, vocabulary, and reading skills to theory of mind development and fables comprehension in children who spoke English as a first language (L1) and children who spoke English as a second language (L2). These factors were examined in 170 preschool children who spoke Arabic, Chinese, Gujarati, Hindi, Punjabi, Tamil, Vietnamese, Urdu, English, or a European language as a first language. All children were being schooled in English. General vocabulary more than any o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…They further found that the learners could generate greater numbers of words with similar meanings that could be substituted for novel words. While, Markel, Major, and Pelletier (2012) indicated that family factors such as parental education and sibling status significantly promoted children's vocabulary skills. Furthermore, they revealed that vocabulary skills could predict L 1 and L 2 learners' performance on comprehension tasks.…”
Section: Vocabulary Learningmentioning
confidence: 99%
“…They further found that the learners could generate greater numbers of words with similar meanings that could be substituted for novel words. While, Markel, Major, and Pelletier (2012) indicated that family factors such as parental education and sibling status significantly promoted children's vocabulary skills. Furthermore, they revealed that vocabulary skills could predict L 1 and L 2 learners' performance on comprehension tasks.…”
Section: Vocabulary Learningmentioning
confidence: 99%
“…One investigation in West Africa reported some success in 3-year-olds on mental state understanding tasks adapted to the culture (Avis & Harris, 1991). Yet, other evidence from South America (Beckmann De Castro Menezes, Da Silva Cruz, Veloso Corrêa, & Brito, 2014;Vinden, 1996), India (Wahi & Johri, 1994) and on Indian immigrant children in Canada (Markel, Major, & Pelletier, 2012) found a delay in understanding the mind. In some cultures, poor social understanding even beyond age 7 is reported (Mayer & Träuble, 2013;Vinden, 1996Vinden, , 1999.…”
mentioning
confidence: 96%